Procesos de la transición urbana a sistemas autónomos descentralizados de energía renovable - Di Pietro, Simone (El Colegio de México A.C., 2022)
The social reconfiguration of technologies and the social and institutional systems that allow their emergence and use is essential for sustainability. This research delves into the urban energy transition processes through the adoption of autonomous / decentralized renewable energy systems, within the dynamics of urban change. The development of this process is strongly dependent on the competition between the actors participating in the urban energy planning process. A methodology based on literature review is used in order to propose a theoretical contribution.